Desensitizing bioactive agents improves bond strength of indirect resin-cemented restorations: preliminary results - Fernanda de Carvalho Panzeri Pires-; Fabíola Fiorezi de Marco; Luciana Assirati Casemiro; Heitor Panzeri (University of São Paulo, 2007)
OBJECTIVE: The aim of this study was to assess the bond strength of indirect composite restorations cemented with a resin-based cement associated with etch-and-rinse and self-etching primer adhesive systems to dentin treated or not with a bioactive material. MATERIALS AND METHOD: Twenty bovine incisor crowns had the buccal enamel removed and the dentin ground flat. The teeth were assigned to 4 groups (n=5): Group I: acid etching + Prime & Bond NT (Dentsply); Group II: application of a bioactive glass (Biosilicato®)+ acid etching + Prime & Bond NT; Group III: One-up Bond F (J Morita); Group IV: Biosilicato® + One-up Bond F. Indirect composite resin (Artglass, Kulzer) cylinders (6x10mm) were fabricated and cemented to the teeth with a dual-cure resin-based cement (Enforce, Dentsply). After cementation, the specimens were stored in artificial saliva at 37ºC for 30 days and thereafter tested in tensile strength in a universal testing machine (EMIC) with 50 kgf load cell at a crosshead speed of 1 mm/min. Failure modes were assessed under scanning electron microscopy. Data were analyzed statistically by ANOVA and Tukey's test (95% level of confidence). RESULTS: Groups I, II and III had statistically similar results (p>0.05). Group IV had statistically significant higher bond strength means (p<0.05) than the other groups. The analysis of the debonded surfaces showed a predominance of adhesive failure mode for Group III and mixed failure mode for the other groups. CONCLUSION: The use of desensitizing agent did not affect negatively the bonding of the indirect composite restorations to dentin, independently of the tested adhesive systems.